From six to ten and beyond: The European Community at the crossroads - Juergen B. Donges (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
The purpose of this paper is to assess the main factors causing the impasse which the EC has reached. The next section examines the lack of consensus of the member states on the aims of the EC and on the means to achieve them. Subsequently, this is related to the EC enlargement. Finally, recommendations will be made on major policy issues in order to provide a new stimulus to the integration process in Western Europe.
Keywords: 330